Governable spaces: A feminist agenda for platform policy - Nathan Schneider (Internet Policy Review, 2022)
Feminist tradition reveals with particular clarity how the online economy has contrived to be both apparently open and persistently unaccountable. Diverse feminist critiques amount to an overlapping insistence that the systems that organize our technology should be governable by the people who rely on them. This article extrapolates from feminist insights and experiences toward a policy agenda for vexing challenges in three domains of the online economy: social-media communities, platform-mediated work, and network infrastructure. The agenda calls for crafting "governable spaces" through diverse and accountable forms of user participation.
Keywords: 300; Feminism; Gig economy; Infrastructure; Social media; Network design; Digital labour platforms